(untitled) (Revista de Ensino em Artes, Moda e Design, 2025)
The present study investigates how synesthesia can be incorporated into the teaching of creativity for fashion designers in training, with the aim of contributing to their personal references and developing original products. Through a narrative review, an attempt was made to understand the concepts of creativity, its characteristics in contemporary times, and how it can be taught. Based on this theoretical foundation, a teaching tool that uses synesthesia to stimulate creativity was proposed and applied in an elective course. The results were analyzed from evaluations conducted in the classroom through data collection and the main result was a fashion collection development with a synesthetic creative process. It is concluded that the inclusion of synesthesia in the creative process can promote genuine inspiration and the development of individuality among designers, in a context marked by copying and lack of encouragement for creation